Phytochemical and Biological Studies of Bark Extract of Miliusa velutina (Dunal) Hook. f. & Thomson (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The main objective of the current research was phytochemical and biological studies of the stem bark of Miliusa velutina (Dunal) Hook. f. & Thomson (Annonaceae). Four purified compounds i.e., friedelin, lupeol, β- sitosterone and caffeic acid were isolated by repeated chromatographic separation and purification of M. velutina. The compounds were identified by analysis of NMR spectral data. The crude dichloromethane extract of stem bark of M. velutina (DEMV) along with its Kupchan partitionates i.e., petroleum ether (PESF), ethyl acetate (EASF), chloroform (CSF) and aqueous (AQSF) soluble fraction were screened for antioxidant, cytotoxic, thrombolytic and antibacterial activities. During the antioxidant activity assay, the AQSF revealed maximum activity with IC50 value of 71.67 μg/ml. The cytotoxicity of plant samples was determined by brine shrimp lethality bioassay, where the maximum cytotoxic activity has been observed for EASF (LC90 = 9.01 μg/ml). In the thrombolytic activity test, the crude dichloromethane extract demonstrated significant efficacy with 46.27% inhibition of clot lysis. In antibacterial screening, the CSF exhibited noticeable inhibitory activity against Shigella boydii with the zone of inhibition 15 mm compared to the standard ciprofloxacin (zone of inhibition = 47 mm).Dhaka Univ. J. Pharm. Sci. 19(2): 125-131, 2020 (December)